Antara Hafalan dan Tulisan: Menyingkap Mekanisme Penjagaan Teks Al-Qur’an dalam Sejarah Islam Awal: Between Memorization and Writing: Uncovering the Mechanisms of Care for Qur'an Text in Early Islamic History - Eka Maryam Shofiyah; Al Komarudin; Ahmad Saerozi (Program Studi Ilmu Al-Quran dan Tafsir STIU Darul Quran, 2026)
This study analyzes the strategic position of the Quran mushaf as a subject in Islamic literature research, with an emphasis on its ongoing processes of preservation and codification. The text asserts that the authenticity of the Quran text to this day is the result of a systematic collaboration between two methods of safeguarding: memorization in the heart (al-hifz fi al-sudur) as the primary form of continuous oral transmission, and writing in a written format (al-hifz fi al-sutur) as a means of documentation and verification. The approach is a qualitative study that analyzes both classical and modern sources, exploring the history of the preservation of the Quranic text, from the time of the Prophet Muhammad (peace be upon him) to the standardization of the mushaf by Uthman. The study results show that this dual system has been functioning well for a long time, providing a strong historical and social basis for claims of the Qurans authenticity. By emphasizing this collaboration, the study aims to respond to and challenge the views of orientalists (such as Wansbrough and Crone) who often question the texts authenticity solely on the basis of written documents. The main conclusion asserts that the truth of the Quranic text is not merely a matter of theological belief but a historical reality explored through a robust and comprehensive preservation system.